Strategi Penerjemahan Metafora pada Novel "L'Etranger" ke Dalam Bahasa Jawa "Wong Njaba" Karya Albert Camus - Rosiana, Agnes Andryani (Jurnal SORA - Pernik Studi Bahasa Asing, 2024)
This study aims to describe the strategy of translating metaphors in the novel “L'Etranger” into the Javanese “Wong Njaba” by Albert Camus. Metaphor is an expression that is often found in literary works. In the translation process, the translation of metaphors is one of the problems that are often encountered by translators, therefore a strategy in the translation of metaphors is absolutely necessary so that the reader can properly capture the message and impression that the author wants to convey. The data source used is the novel “L'Etranger” and its translation, “Wong Njaba”. The data used are metaphorical expressions and their translations. The data collection method used in this study is simak with techniques of catat. The results show that the metaphor translation strategy used by the translator is that (Source Language) SL metaphor is translated into the same metaphor in (target Language) TL, metaphor in SL is translated into simile in TL, SL metaphor is translated become different metaphors in SL but have the same meaning, and metaphors in SL which are translated into non-metaphorical expressions.